Social studies course and values education - Kan, Çi?dem (My University, 2010)
Common good values need to be existent and transferred to new generations for forming up a proper social structure. Education has many important roles in such a process. Values are personal, ethical and social feelings keeping people and the whole society alive. As for the social studies course, it has an important role in terms of its community-related content and transferring values. Present study has been carried out in order to reveal importance of social studies course in terms of teaching of values. Literature review was also used in the research. Literature screening method has been employed in the research.
Sosyal bilgiler dersi ve de?erler e?itimi
Keywords: Education; Social studies; Values